Erratum to: Sensitivity limit investigation of a Sagnac gyroscope through linear regression analysis - Angela D. Di Virgilio; Carlo Altucci; Francesco Bajardi; Andrea Basti; Nicolò Beverini; Salvatore Capozziello; Giorgio Carelli; Donatella Ciampini; Francesco Fuso; Umberto Giacomelli; Enrico Maccioni; Paolo Marsili; et al. (European Physical Journal C: Particles and Fields, 2021)
A Correction to this paper has been published: https://doi.org/10.1140/epjc/s10052-021-09199-1